(untitled) (La U Investiga, 2024)
Hematometra is the uterine retention of menstrual blood that was not evacuated through the cervix, it is a condition that occurs in 6.7% of all women, it can be of congenital cause due to transverse vaginal septum and perforated hymen, or acquired, such as cervical neoplasias and previous surgeries of the uterus. Among the common symptoms are primary or secondary amenorrhea and constant pelvic abdominal pain, on the other hand, in relation to menopausal women, the clinical picture is usually asymptomatic. Imaging resources are essential for the diagnosis of hematometra and help to estimate its volume and possible cause. Therapeutic management of hematometra includes: the use of GnRH analogues, cervical dilation to drain accumulated blood or in cases where the retained fluid is suspected to be infected. Another option is biopsy, which should be postponed for two weeks to reduce the chances of infection or uterine perforation, and hysterectomy in cases of definitive treatment. In this case, given that the patient has cervical stenosis, a biopsy cannot be performed and it is decided to perform surgical treatment with total abdominal hysterectomy to obtain the definitive histopathological result. The patient recovers favorably postoperatively and is sent with High medical.